Management of the Pasaman Regency Fisheries and Food Service in Implementing the Aquaculture Village Programme - Rahmadani, Rahmadani; Yulivestra, Malse; Putri, Annisa Aulia (Jurnal Administrasi dan Kebijakan Publik, 2025)
The Aquaculture Village Program is a program initiated directly by the Ministry of Maritime Affairs and Fisheries through Ministerial Regulation No. 47 of 2021 aimed at increasing the production and productivity of fish farming and improving the welfare and income of fish farmers, including in Pasaman Regency. Therefore, effective and appropriate management is essential for its successful implementation. The method in this research is qualitative with a descriptive approach. Data collection techniques through observation, interviews, and documentation. The results of this study found that the Management of the Fisheries and Food Service Office in Implementing the Fisheries Village Program is technically good enough, but not optimal. There are findings in planning on program policies/regulations, namely Ministerial Regulation Number 47 of 2021 which is not clearly guided and tends to only guide Decree Number 64 of 2021, Management of Fish Seed Center infrastructure that has not been maximized because it has not been supported by adequate funding and marketing (market) of superior fish commodities, namely Carp, which has not developed and tends to stagnate because it is influenced by reduced demand for fish in the market, as well as indirect supervision that is not administratively corrected by the Fisheries and Food Service as the implementer of the Aquaculture Village Program. Therefore, it is recommended that the Pasaman Regency Fisheries and Food Service evaluate and take corrective action in supporting the implementation of Aquaculture Village Program